Synthesis of azomethine-containing bisphenols with perfluorinated mono- and biphenylene moieties - Shevchenko, V.V.; Tkachenko, I.M.; Kobzar, Ya.L.; Shekera, O.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
By the interaction of aromatic diamines containing fragments of tetrafluorobenzene and octafluorobiphenyl with salicylic aldehyde, perfluoroaromatic azomethine containing bisphenols, as monomers for the synthesis of functional polymers, are obtained. Their structures and spectroscopic properties are studied by methods of IR, 1H and 19F NMR, and UV-vis spectroscopy.